Vapour phase co‐deposition of Al—Cu thin film alloys. Issue 5 (2nd May 2013) - Hafner, Martina; Mardare, Andrei Ionut; Hassel, Achim Walter
Abstract The fabrication and characterisation of Al—Cu thin film alloys obtained using co‐deposition geometry from individual Al and Cu sources were addressed. A compositional gradient ranging from 36 to 93 at.% Cu was obtained. The surface microstructure evolved with a strong influence on the Cu content. This was connected to the presence of the Cu(111) in the alloys. The electrical resistivity showed a decrease by almost one order of magnitude in the Cu rich region of the Al—Cu combinatorial library. Al—Cu thin films evaporated from a single source produced a surface compositional gradient of 7 at.%. X‐ray photoelectron spectroscopy (XPS) depth profiling revealed an in‐depth compositional gradient as well. This behaviour was attributed to the gas phase dynamics of Al and Cu during the thin film formation. <inline-graphic xlink:href="ark:/27927/pgg20q11w9q" content-type="pssa201200781-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />